Protein kinase C inhibitor Gö6976 but not Gö6983 induces the reversion of E- to N-cadherin switch and metastatic phenotype in melanoma: identification of the role of protein kinase D1 - Messaouda Merzoug-Larabi (3619421) (2017)
Background Melanoma is a highly metastatic type of cancer that is resistant to all standard anticancer therapies and thus has a poor prognosis. Therefore, metastatic melanoma represents a significant clinical problem and requires novel and effective targeted therapies. The protein kinase C (PKC) family comprises multiple isoforms of serine/threonine kinases that possess distinct roles in cancer development and progression. In this study, we determined whether inhibition of PKC could revert a major process required for melanoma progression and metastasis; i.e. the E- to N-cadherin switch. Methods The cadherin switch was analyzed in different patient-derived primary tumors and their respective metastatic melanoma cells to determine the appropriate cellular model (aggressive E-cadherin-negative/N-cadherin-positive metastasis-derived melanoma cells). Next, PKC inhibition in two selected metastatic melanoma cell lines, was performed by using either pharmacological inhibitors (Gö6976 and Gö6983) or stable lentiviral shRNA transduction. The expression of E-cadherin and N-cadherin was determined by western blot. The consequences of cadherin switch reversion were analyzed: cell morphology, intercellular interactions, and β-catenin subcellular localization were analyzed by immunofluorescence labeling and confocal microscopy; cyclin D1 expression was analyzed by western blot; cell metastatic potential was determined by anchorage-independent growth assay using methylcellulose as semi-solid medium and cell migration potential by wound healing and transwell assays. Results Gö6976 but not Gö6983 reversed the E- to N-cadherin switch and as a consequence induced intercellular interactions, profound morphological changes from elongated mesenchymal-like to cuboidal epithelial-like shape, β-catenin translocation from the nucleus to the plasma membrane inhibiting its oncogenic function, and reverting the metastatic potential of the aggressive melanoma cells. Comparison of the target spectrum of these inhibitors indicated that these observations were not the consequence of the inhibition of conventional PKCs (cPKCs), but allowed the identification of a novel serine/threonine kinase, i.e. protein kinase Cμ, also known as protein kinase D1 (PKD1), whose specific inhibition allows the reversion of the metastatic phenotype in aggressive melanoma. Conclusion In conclusion, our study suggests, for the first time, that while cPKCs don’t embody a pertinent therapeutic target, inhibition of PKD1 represents a novel attractive approach for the treatment of metastatic melanoma. Other Information Published in: BMC Cancer License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: https://dx.doi.org/10.1186/s12885-016-3007-5